Investigating factors influencing utilization of trauma-focused cognitive behavioral therapy among unaccompanied young refugees: an exploratory analysis - Barbara Kasparik; Madina Farani; Elisa Pfeiffer; Cedric Sachser; Rita Rosner (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Unaccompanied young refugees (UYRs) exhibit elevated levels of mental distress, including posttraumatic stress symptoms (PTSS), depression and anxiety. Despite the considerable psychological burden, UYRs frequently lack access to mental health care (MHC). The factors that contribute to higher rates of treatment utilization among UYR remain poorly understood. Untreated PTSS can result in chronic impairment, underscoring the importance of identifying these factors. The aim of this study is to investigate factors associated with the intention and actual utilization of MHC of UYRs living in child and youth welfare facilities in Germany. Method This study is part of the multi-site project BETTER CARE which aims to implement a stepped and collaborative care approach. A sample of N = 139 UYRs who had received a treatment recommendation for trauma-focused cognitive behavioral therapy (TF-CBT) was analyzed. Binomial logistic regression was performed to identify factors predicting the likelihood of intention to seek MHC. In addition, the association between intention to seek MHC and actual utilization was determined using a chi square test. Results The results demonstrated a significant correlation between age (η = 0.25, p <.01), length of stay in Germany (η = 0.28, p <.01), and severity of PTSD symptoms (η = 0.26, p <.01) with intention to use MHC. In the logistic regression analysis, PTSD emerged as a significant predictor of intended use (B = 2.66, p <.05). The utilization of MHC was found to be closely associated with the initial intention to use (χ²(1) = 88.846, p <.001). Conclusions The findings contribute to an expanding body of literature on the mental health requirements and service utilization patterns among UYRs, offering insights for policymakers, mental health professionals, and child welfare services striving to enhance care for this vulnerable population.